1970
DOI: 10.1177/004051757004000602
|View full text |Cite
|
Sign up to set email alerts
|

Waves in Tires

Abstract: 498increases 'linearly with increasing fabric thickness but then approaches an asymptotic maximum. The implication is, therefore, that, although the heat generated increases linearly with fabric thickness, heat dissipation also increases with increasing temperature, so that the net increase in needle temperature with thick-'ness is less than linear. ' Although the results are exploratory, they do present some insight into the nature of the needle heating problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, though standing waves "rst appear at a speed near A for small damping, they persist for all higher rotation frequencies. To quote reference [1], &&It is not possible to drive through to a higher speed where the tire again runs smoothly (i.e., without large standing waves).'' As observed in experiment and as predicted by our analysis, the size and shape of the standing wave vary monotonically with rotation speed in the range studied.…”
Section: Physical Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, though standing waves "rst appear at a speed near A for small damping, they persist for all higher rotation frequencies. To quote reference [1], &&It is not possible to drive through to a higher speed where the tire again runs smoothly (i.e., without large standing waves).'' As observed in experiment and as predicted by our analysis, the size and shape of the standing wave vary monotonically with rotation speed in the range studied.…”
Section: Physical Interpretationmentioning
confidence: 99%
“…In addition to its intrinsic interest as a problem in the dynamics of solids, the critical speed phenomenon represents a serious performance limitation for high-speed vehicles, since the large strains associated with the standing waves invariably lead to signi"cant working of the tire material and hasten tire failure. Useful reviews can be found in reference [1], which covers work prior to 1970, as well as in reference [2], which brings together many issues related to tires, from materials to dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of tyre standing waves has been studied since the 1950s [1,2], and a useful review of early experimental and theoretical works (published before 1970) can be found in the paper of Ames [3]. Starting from the work of Turner [2], there have been many attempts at theoretical modelling of this phenomenon (see also [3] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the work of Turner [2], there have been many attempts at theoretical modelling of this phenomenon (see also [3] and references therein). However, for the sake of simplicity, in most of the early works the authors did not consider the phenomenon of standing waves in tyres as wave generation problem, but rather argued from a wave propagation viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…The standing waves phenomenon has been investigated since the 1950s for traffic security reasons. A review of early theoretical and experimental studies until 1970 is presented in [1]. There have been many attempts for mathematical modelling of the standing waves phenomenon.…”
Section: Introductionmentioning
confidence: 99%